PENGABDIAN MASYARAKAT MAHASISWA UMKM TERHADAP INDUSTRI UMKM (PITCH PRADA) - Nashita Shakila Hendratmo; Fadya Hanifa; Sumaryanto (CV. ITTC INDONESIA, 2025)
The community service program through Pitch Prada aims to empower micro and small-scale MSMEs by focusing on strengthening information systems, managerial accounting, legal compliance, and organizational structure. The method employed is descriptive qualitative with a participatory approach, where students are directly involved as mentors and facilitators in developing financial recording systems, implementing job costing orders, and guiding business owners in preparing financial reports and legal documents such as tax identification numbers (NPWP) and OSS registration. The results of the program show a significant increase in MSME actors' awareness of the importance of financial documentation, pricing accuracy based on cost of goods sold (COGS), and professionalism in business management through clearer and more efficient work structures. This program not only delivers a positive impact on MSMEs but also fosters students’ social empathy and managerial competencies as agents of change in inclusive economic development.